The Current Role of Graphene-Based Nanomaterials in the Sample Preparation Arena - Maciel, Edvaldo Vasconcelos Soares; Mejía-Carmona, Karen; Jordan-Sinisterra, Marcela; da Silva, Luis Felipe; Vargas Medina, Deyber Arley; Lanças, Fernando Mauro (Frontiers in Chemistry, 2020)
Since its discovery in 2004 by Novoselov et al., graphene has attracted increasing attention in the scientific community due to its excellent physical and chemical properties, such as thermal/mechanical resistance, electronic stability, high Young's modulus, and fast mobility of charged atoms. Besides, other remarkable characteristics support its use in analytical chemistry, especially as sorbent. Therefore, graphene-based materials (GBMs) have been currently used as a promising sorbent in sample preparation. Graphene and graphene oxide, owing to their excellent physical-chemistry properties as a large surface area, good mechanical strength, thermal stability, and delocalized π-electrons are ideal sorbents, especially for molecules containing aromatic rings. They have been used as sorbents in several sample preparation techniques such as solid-phase extraction (SPE), stir bar sorptive extraction (SBSE), magnetic solid-phase extraction (MSPE) as well as in miniaturized modes as solid-phase microextraction (SPME) in different configurations. Recent studies have demonstrated superior sorption and recoveries by graphene-based sorbents when compared to other classical sorbents as C8 and C18-bonded silica, for instance. Although their remarkable adsorption capacity, small amounts of graphene-based sorbents should be used to avoid incomplete analytes desorption; as a result, this can limit their use in some sample preparation techniques. Likewise, owing to their reduced size, the graphene sheets commonly aggregate to each other, causing clogging in some high-pressure extractive devices, which can also limit their use. One way to overcome these and other drawbacks consists of covalently attach the graphene sheets to proper support material (e.g., silica, polymers, magnetically modified supports). Besides, graphene-based materials can be further modified to favor some interactions with specific analytes, resulting in more efficient sorbents with higher selectivity for specific chemical classes. For instance, functionalization with cyclodextrins increases the selectivity and efficiency for chiral molecules. As a result of this wide variety of more selective sorbents, several studies have shown the current potential of applying GBMs in different fields such as food, biological, pharmaceutical, and environmental applications. This review focus on the current use of several graphene-based materials in sample preparation techniques highlighting their synthesis, chemical structure, and potential application for the extraction of target analytes in different complex matrices